Sodium Intake, Fluid Balance and Nutritional Status Impact on The Event of Shortness based on Respiration Rate (RR) in Congestive Heart Failure (CHF) Patients - abdurrachim, rijanti (Poltekkes Kemenkes Yogyakarta, 2024)
Riskesdas 2018 data, the prevalence of heart disease in Indonesia is 1.5%. Congestive Heart Failure (CHF) is the inability of the heart to pump blood to meet the needs of oxygen and nutrients to the body's tissues. The most common symptom of recurrence is shortness of breath. One of the dietary managements of CHF patients is the limitation of sodium and fluid. The study aimed to determine sodium intake, fluid balance and nutritional status in the occurrence of shortness of breath based on Respiration Rate (RR) in Congestive Heart Failure (CHF) patients in Cardiac Hospitalization at H. Moch. Ansari Saleh Banjarmasin. This study was conducted through the an observational analytic with a prospective approach. The samples were 12 people with CHF who were hospitalized in RSUD H. Moch. Ansari Saleh Banjarmasin from April 16 to May 6, 2018. taken based on inclusion and exclusion criteria. The data was collected using a 1x24 hour food recall form, a liquid form and a Respiration Rate form.The collected data was further analyzed by using the Spearman rank correlation test with a 95% confidence level. The study has found that there is a correlation between sodium intake (p = 0.049) and fluid balance (p = 0.01) to the occurrence of shortness of breath based on the RR value of CHF patients and not significant for nutritional status. Based on the finding, therefore, adjusting sodium intake and fluid balance is useful to reduce symptoms of shortness of breath in CHF patients. KEYWORDS : Congestive Heart Failure (CHF), Sodium Intake, Fluid Balance , Shortness of Breath